(untitled) (RT. A Journal on Research Policy and Evaluation, 2015)
The aim of this paper is to describe the impact of research on society, economy and culture in the Humanities and Social sciences. In the first part of the paper, we describe the principal characteristics of the evaluation of research impact in the United Kingdom (UK), with a special focus on the new national exercise of research evaluation: the ‘Research Excellence Framework’ (REF2014). In the second part of the paper we present a case study in a British university campus where good practices of impact evaluation have been recently introduced. The main results of this study show that impact evaluation of Social sciences and Humanities research is a today’s key challenge for the academia, especially due to the difficulty in identifying the appropriate indicators for research impact measurement. Finally, we present the main themes of the current debate about the evaluation of the impacts in different fields of research.